2021
DOI: 10.1371/journal.pone.0244556
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of calcium regulation, electron transport, and mitochondrial protein translation are molecular signatures of susceptibility to recurrent exertional rhabdomyolysis in Thoroughbred racehorses

Abstract: Recurrent exertional rhabdomyolysis (RER) is a chronic muscle disorder of unknown etiology in racehorses. A potential role of intramuscular calcium (Ca2+) dysregulation in RER has led to the use of dantrolene to prevent episodes of rhabdomyolysis. We examined differentially expressed proteins (DEP) and gene transcripts (DEG) in gluteal muscle of Thoroughbred race-trained mares after exercise among three groups of 5 horses each; 1) horses susceptible to, but not currently experiencing rhabdomyolysis, 2) healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…STIM1 regulates store operated calcium entry into the muscle cell when sarcoplasmic reticulum stores are depleted [ 50 ]. CASQ1 is a high affinity calcium storage protein in the sarcoplasmic reticulum that was a ↑DEP and ↓DEG in RER-susceptible Thoroughbred mares and a ↓DEG in RER-susceptible Thoroughbred geldings between episodes of rhabdomyolysis in previous studies [ 7 , 51 ]. Enhanced sarcoplasmic reticulum calcium stores and post-translational modulation of RYR1 calcium release by oxidation (S-nitrosylation) or beta-adrenergic-induced phosphorylation are potential mechanisms that could enhance RYR1 calcium release and trigger an episode of rhabdomyolysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…STIM1 regulates store operated calcium entry into the muscle cell when sarcoplasmic reticulum stores are depleted [ 50 ]. CASQ1 is a high affinity calcium storage protein in the sarcoplasmic reticulum that was a ↑DEP and ↓DEG in RER-susceptible Thoroughbred mares and a ↓DEG in RER-susceptible Thoroughbred geldings between episodes of rhabdomyolysis in previous studies [ 7 , 51 ]. Enhanced sarcoplasmic reticulum calcium stores and post-translational modulation of RYR1 calcium release by oxidation (S-nitrosylation) or beta-adrenergic-induced phosphorylation are potential mechanisms that could enhance RYR1 calcium release and trigger an episode of rhabdomyolysis.…”
Section: Discussionmentioning
confidence: 99%
“…In further agreement with the study of acute rhabdomyolysis in French Trotters, numerous mitochondrial genes were downregulated in RER-susceptible horses in our study [ 9 ]. In the acute rhabdomyolysis study, this was interpreted to indicate a decrease in mitochondrial protein expression arising from mitochondrial buffering of calcium as was found in Thoroughbreds susceptible to RER [ 7 , 9 ]. Our proteomic analysis, however, found that 89% (17/19) of the DEP mitochondrial proteins were upregulated and the genes encoding 11 of these proteins had significantly downregulated gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Skeletal muscle glutathione concentrations were measured previously in several species with wide-ranging results depending on the method of analysis ( Table S1 ) [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. When predominantly fast-twitch muscle such as the human vastus lateralis or “quadriceps” (~60% fast-twitch muscle fiber; glutathione 1.2–1.4 nmol/mg wet weight) [ 42 ] were compared to Thoroughbred gluteal muscle (~80% fast-twitch muscle fibers 0.85 nmol/kg wet weight) [ 43 ] measured by HPLC, horses appeared to have approximately 40% lower glutathione concentrations than humans. This could be in part be due to the higher fast-twitch fiber type composition of horse gluteal muscle compared to human vastus lateralis or, intriguingly, equine muscle could have a lesser capacity to synthesize glutathione or an enhanced turnover of glutathione with exercise.…”
Section: Discussionmentioning
confidence: 99%